Advancements in MEMS Micromirror and Microshutter Arrays for Light Transmission Through a Substrate - Shilby Baby; Mustaqim Siddi Que Iskhandar; Md Kamrul Hasan; Steffen Liebermann; Jiahao Chen; Hasnain Qasim; Shujie Liu; Eslam Farrag; Dennis Löber; Naureen Ahmed; Guilin Xu; Hartmut Hillmer (Micromachines)
This paper reviews and compares electrostatically actuated MEMS (micro-electro-mechanical system) arrays for light modulation and light steering in which transmission through the substrate is required. A comprehensive comparison of the technical achievements of micromirror arrays and microshutter arrays is provided. The main focus of this paper is MEMS micromirror arrays for smart glass in building windows and façades. This technology utilizes millions of miniaturized and actuatable micromirrors on transparent substrates, enabling use with transmissive substrates such as smart windows for personalized daylight steering, energy saving, and heat management in buildings. For the first time, subfield-addressable MEMS micromirror arrays with an area of nearly 1 m2 are presented. The recent advancements in MEMS smart glass technology for daylight steering are discussed, focusing on aspects like the switching speed, scalability, transmission, lifetime study, and reliability of micromirror arrays. Finally, simulations demonstrating the potential yearly energy savings for investments in MEMS smart glazing are presented, including a comparison to traditional automated external blind systems in a model office room with definite user interactions throughout the year. Additionally, this platform technology with planarized MEMS elements can be used for laser safety goggles to shield pilots, tram, and bus drivers as well as security personal from laser threats, and is also presented in this paper.